Expression of Integrin Alpha10 Is Induced in Malignant Melanoma - Ann-Kathrin Wenke; Christian Kjellman; Evy Lundgren-Akerlund; Christian Uhlmann; Nikolas K. Haass; Meenhard Herlyn; Anja K. Bosserhoff (Cellular Oncology)
Recently, integrin alpha10 was described as a collagen type II-binding integrin expressed mainly in chondrocytes. However, by array studies we detected integrin alpha10 also to be upregulated in malignant melanoma compared to primary melanocytes. Subsequent analysis of melanoma cell lines and melanoma tumor samples confirmed this finding. Further, we demonstrated that expression of integrin alpha10 is controlled by AP-2 and Ets-1, two transcription factors known to be involved in melanoma development and progression. To investigate the functional relevance of integrin alpha10, expression was downregulated via stable antisense transfection. Proliferation assays and colony forming assays revealed no differences comparing antisense integrin alpha10 cell clones with control and wild type melanoma cells, respectively. However, antisense integrin alpha10 cell clones and Mel Im cells treated with an inhibitory antibody against integrin alpha10 showed a reduced migratory potential.